Effect of Seed Treatment (Soaking Cum Incubation) on Plant Population Maintenance of Maize (Zea Mays L) under Rainfed Conditions during Winter Season at Parwanipur, Bara, Nepal - Yadav, B.P.; Yadav, D. N.; Koirala, K.B.; Pandey, K.R.; Thapa, R.B. (International Journal of Applied Sciences and Biotechnology, 2016)
Non-primed top quality seed of maize having cent-percent germination in lab resulted only 61% emergence in the field based on 4806 observations for non-primed seed while treated seed (priming cum incubation) recorded 82 % emergence in the field based on 4806 observations during first year. During second year experiment also non-primed top quality seed of hybrid maize having cent-percent germination in lab resulted 71.29% emergence while priming cum incubation treatment recorded 91.84% emergence. The result of both years clearly indicates the importance of seed treatment for maintaining the optimum plant population and there by insuring higher yield of winter hybrid maize. Int J Appl Sci Biotechnol, Vol 4(1): 113-116